Exploring the Role of Fathers in the Lives of Children in Eswatini - Dlamini, Bakhe; Mpofu, Phumuzani (Studies in Learning and Teaching, 2025)
The absence of fathers is a widespread issue that quietly undermines communities across the globe, and the Kingdom of Eswatini is no exception. This study aimed to explore how fathers contribute to their children's growth, identify barriers to their involvement, and propose strategies to foster greater paternal engagement in parenting. A transformative qualitative design was employed, utilizing purposive sampling to select participants. The sample consisted of four juvenile schoolteachers two males and two females, four male inmates aged between 20 and 35, four young adults aged between 20 and 25, and four parents (both fathers and mothers). Data was gathered through semi-structured and focus group interviews, which were analyzed thematically to uncover key insights. In response to our first research question, the study found that fathers contribute to their children’s development by: 1) providing basic needs, 2) instilling discipline, 3) offering positive role models, 4) ensuring emotional stability, 5) showing love, and 6) protecting their children. Regarding the second research question, which explored the reasons why fathers may not be supporting their children, the following barriers emerged: 1) involvement with new partners, 2) children being used to settle parental disputes, 3) inherent negligence in some fathers, 4) lack of financial resources, 5) insufficient grooming on how to be a responsible father, and 6) disputed paternity. For the final research question, which focused on strategies to enhance father involvement, the following themes were identified: 1) awareness programs on the importance of father involvement in a child’s life, 2) educating parents, especially women, to avoid using children in conflicts, 3) conducting DNA tests in cases of disputed paternity, and 4) encouraging current fathers to serve as good role models.